Activation of subnanometric Pt on Cu-modified CeO2 via redox-coupled atomic layer deposition for CO oxidation - Xiao Liu (Nature Portfolio, 2020)
Improving low-temperature activity and noble-metal efficiency remains a challenge for next generation exhaust catalysts. Here, the authors achieve the activation of subnanometric Pt on Cu-modified CeO2 for low-temperature CO oxidation with an onset below room temperature.